2022
DOI: 10.1111/aor.14457
|View full text |Cite
|
Sign up to set email alerts
|

Hemadsorption in patients requiring V‐A ECMO support: Comparison of Cytosorb versus Jafron HA330

Abstract: Background ECMO support is associated with the development of a systemic hyper‐inflammatory response, which may become quite significant and extreme in some cases. We hypothesize that Cytosorb or Jafron therapy may benefit patients on V‐A ECMO in terms of levels of inflammatory markers such as IL‐6, complications, and overall outcomes. Methods We conducted a retrospective study of prospectively collected data in a single tertiary care center between January 2021 and April 2022. At the time of the analysis of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 32 publications
0
1
0
Order By: Relevance
“…Table 1 (Ref. [ 14 , 15 , 16 , 19 , 20 , 21 ]) provides the details of the included studies. The included studies were published in the year 2022, one study presented a randomized population [ 22 ] and the others were observational cohort studies.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Table 1 (Ref. [ 14 , 15 , 16 , 19 , 20 , 21 ]) provides the details of the included studies. The included studies were published in the year 2022, one study presented a randomized population [ 22 ] and the others were observational cohort studies.…”
Section: Resultsmentioning
confidence: 99%
“…Although there are several studies on the use of Cy-tosorb® in the context of v.a. ECMO therapy or LVAD implantation in patients with heart failure, their results have been inconsistent [14,15]. Another hemoadsorbtion device (e.g., HA380, Jafron, Zhuhai City, Guangdong, China) has been also designed aiming at reducing the systemic inflammatory response and improving postoperative recovery [16], however its use in patients with heart failure has been limited so far.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, it was observed that the mortality rate in the control group was higher compared to the cytokine adsorption groups (60% vs. 20%, p = 0.02). After a 72-hour period in intensive care, there was a noticeable decrease in blood in ammation markers 17 . Additionally, a comprehensive review of the relevant literature has consistently shown an increasing use of hemoadsorption in patients undergoing extracorporeal cardiopulmonary resuscitation (ECPR).…”
Section: Discussionmentioning
confidence: 99%
“…It has the potential to reduce the occurrence of AKI and decrease the need for renal replacement therapy. Further research is needed to validate these findings and assess long-term outcomes [15]. In summary, several studies have reported positive outcomes with CytoSorb in emergency cardiac surgery, including shorter operative times, lower blood transfusions, and shorter intensive care unit stays.…”
Section: A Pilot Study By M Diab Et Al Called Remove-pilot Compared C...mentioning
confidence: 95%